Multiple regeneration of clinacanthusnutans nodal explants by using 6-Benzylaminopurine (BAP) Hormone / Siti Zulaiha Ghazali and Saiyidah Nafisah Hashim - Siti Zulaiha, Ghazali; Saiyidah Nafisah, Hashim (2015)
Clinacanthusnutans is a medicinal plants currently found to be able to treat cancer. This plant can be found mostly in China, Thailand and Malaysia. Since a large portion of pharmaceutical drugs are derived, the demand for these raw materials is steadily rising. In order to fulfill the demand on the numbers of C. nutans plant in the drug production, multiple regenerations by plant tissue culture technique is applied and production of undifferentiated callus were done. Culture environmental condition was controlled and sterile nodal explants were inoculated in a MurashigeSkoog (MS) media supplemented with plant hormone cytokinin, BAP (6 - Benzylaminopurine) at different concentrations (0 mg/L, 1.0 mg/L, 1.5 mg/L, and 2.0 mg/L). Plants were subcultured at every 4 weeks and sterile grown plants were used asexplants to grow highly proliferated callus at different media concentration. Callus inductions were also tested at two different time period. The observation of the regeneration was observed and analyzed after 8 weeks. Results showed MS media with 2.0 mg/L BAP gave the highest regeneration, mean number leaves and height of explants formation with 11.20 ± 0.374 and 5.260 ± 0.404 respectively. Besides that, at 2.0 mg/L concentration, the explants show the formation of roots after 7 weeks. The formulated media in regenerating this valuable herbal plant with anticancer beneficiary compound will give a significant contribution to the society.